The CHEK2 Variant C.349A>G Is Associated with Prostate Cancer Risk and Carriers Share a Common Ancestor - Brandao A; Paulo P; Maia S; Pinheiro M; Peixoto A; Cardoso M; Silva MP; Santos C; Eeles RA; Kote-Jarai Z; Muir K; Schleutker J; et al. (MDPI, 2022)
Simple SummaryIt is well-recognised the strong contribution of genetic factors to prostate cancer (PrCa) susceptibility, thus genetic screening is critical for presymptomatic diagnosis and identification of individuals at high-risk. In this context, recurrent founder variants in cancer predisposing genes, by providing specific targets for early identification of carriers at risk of developing the disease, may be leveraged to implement cost-efficient targeted genetic screening strategies. The goal of this study was to investigate whether CHEK2 c.349A>G, the only recurrent "likely pathogenic" variant in CHEK2 gene reported in the Portuguese population, plays an important role in PrCa development, and the possibility of a founder effect behind its origin. Our results clearly demonstrate that c.349A>G in the CHEK2 tumour-suppressor gene is a founder variant significantly associated with an increased risk of PrCa, suggesting its potential usefulness for cost-effective targeted genetic screening in PrCa families.The identification of recurrent founder variants in cancer predisposing genes may have important implications for implementing cost-effective targeted genetic screening strategies. In this study, we evaluated the prevalence and relative risk of the CHEK2 recurrent variant c.349A>G in a series of 462 Portuguese patients with early-onset and/or familial/hereditary prostate cancer (PrCa), as well as in the large multicentre PRACTICAL case-control study comprising 55,162 prostate cancer cases and 36,147 controls. Additionally, we investigated the potential shared ancestry of the carriers by performing identity-by-descent, haplotype and age estimation analyses using high-density SNP data from 70 variant carriers belonging to 11 different populations included in the PRACTICAL consortium. The CHEK2 missense variant c.349A>G was found significantly associated with an increased risk for PrCa (OR 1.9; 95% CI: 1.1-3.2). A shared haplotype flanking the variant in all carriers was identified, strongly suggesting a common founder of European origin. Additionally, using two independent statistical algorithms, implemented by DMLE+2.3 and ESTIAGE, we were able to estimate the age of the variant between 2300 and 3125 years. By extending the haplotype analysis to 14 additional carrier families, a shared core haplotype was revealed among all carriers matching the conserved region previously identified in the high-density SNP analysis. These findings are consistent with CHEK2 c.349A>G being a founder variant associated with increased PrCa risk, suggesting its potential usefulness for cost-effective targeted genetic screening in PrCa families.